English as a Foreign Language (EFL) learning assessment in single-sex and co-educational classrooms - Umi Farisiyah; Badrun Kartowagiran; Aminuddin bin Hassan (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2021)
This study investigates the effects of Single-Sex and Co-educational classrooms on English learning outcomes. This study is a causal-comparative study in ex post facto design. The sample is three classes consisting of 73 students (boy and girl-single-sex classes and a co-educational class) from a private secondary school in Central Java, Indonesia. An integrated English test was used, equating the 2013 curriculum and CEFR for English. It tested four skills in English consisting of Listening, Speaking, Reading, and Writing. Expert judgments have already checked the instrument through face validity. Item internal consistency from all skills was good, and the reliability was too, in a good category. This study indicates that organizing a Single-sex classroom in the English learning process has a positive and significant effect on English achievement. Being in a Single-Sex classroom benefitted the students in their outcomes in learning English. This study also implies that teachers, especially English teachers, must understand their students' learning strategies to implement the appropriate learning strategies. It is because male and female students learn something in different ways